Chitosan-based core-shell nanomaterials for pH-triggered release of anticancer drug and near-infrared bioimaging. (10th February 2017) - Tan, Lianjiang; Huang, Ran; Li, Xiaoqiang; Liu, Shuiping; Shen, Yu-Mei; Shao, Zhifeng
Highlights: Modified chitosan exhibits pH-responsive structural transformation. Chitosan-based core-shell nanospheres can release DOX triggered by lowered pH. The NIR-fluorescent nanospheres can be monitored in real time by NIR imaging. DOX release from nanospheres can be activated in tumor cells for cancer therapy. Abstract: As a naturally-abundant biopolymer, chitosan (CS) exhibit pH-sensitive structural transformation within a narrow pH range. Integrating hydrophobic groups to CS molecules gives modified CS polymers with more adjustable pH responsiveness. In this paper, near-infrared (NIR) photoluminescent Ag2 S QDs capped by long-chain carboxylic acid were synthesized and then conjugated with CS via esterification reaction. The anticancer drug doxorubicin (DOX) has an affinity for the hydrophobic oleoyl groups and was entrapped by them to produce Ag2 S(DOX)@CS nanospheres. A variety of experiments were performed to characterize the nanospheres. In vitro and in vivo experiments showed that the nanospheres can release DOX at lowered pH in tumor cells and have high antitumor efficacy. In addition, the strong NIR signal derived from the encapsulated Ag2 S QDs makes real-time monitoring of the nanosphere distribution in a body possible. This study provides a new CS-based nanocomposite drug carrier for efficient cancer therapy.